Efektifitas “magic cool” aromaterapi lavender terhadap penurunan skor nyeri dismenorea - Eka Oktavianto; Endar Timiyatun; Suryati Suryati (Health Sciences and Pharmacy Journal, 2021)
Symptoms of dysmenorrhea are experienced by many teenage girls, especially on the first and second day of menstruation. These symptoms are considered very disturbing activities of daily living, especially school activities. The use of magic-cool lavender aromatherapy is thought to be effective in reducing dysmenorrhea pain and providing comfort. This study was conducted to determine the effectiveness of giving magic-cool lavender aromatherapy to reduce dysmenorrhea pain in adolescents.This research was a pre-experimental study with a one group pre-post test design without control. The respondents were adolescents aged 17-20 years who experienced dysmenorrhea on the first and second day of menstruation. The sampling technique used was accidental sampling and obtained 40 respondents. Measurement of pain intensity using a Numeric Rating Scale (NRS) questionnaire. Before to do the treatment, the respondents were assessed for their pain scores (pre-test). Then given treatment in the form of magic-cool aromatherapy with 5 drops of lavender essential oil applied to a cold and damp handkerchief rubbed on the face, neck and hands while inhaling the aroma for 15 minutes. After that, the pain score was re-assessed (post-test). Analysis of the data used was the paired sample t-test (t-dependent test). Before being given treatment the average dysmenorrhoea pain scale was 7.40, after being given the intervention for the first 5 minutes the average dysmenorrheal scale dropped to 6.30, then given the second 5 minute intervention and there was a decrease with an average scale of 5.0, after that the intervention was continued Back in the third 5 minutes there was a decrease in pain with an average scale of 3.6. The mean value was -3.8, the t value was 10.56 and the p value was 0.000 (p value 0.05). The conclusion in this study was giving of magic-cool lavender aromatherapy is effective in reducing dysmenorrhea pain in adolescents (p value 0.05).